Saving the mango crop - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1986)
Spraying mangoes on the tree does not prevent all disease infections which may cause fruit which look good at harvest time to go bad before it reaches market. Now there is a machine designed to combat post-harvest fruit infections by dipping...